PENGARUH PENGALAMAN, TAAT TERHADAP STANDAR HUKUM, REPUTASI, INDEPENDENSI DAN KOMITMEN YANG KUAT TERHADAP KEPUASAN KLIEN KANTOR AKUNTAN PUBLIK (Studi Empiris pada Perusahaan Industri Keuangan Non Bank di Pekanbaru yang tercatat di Otoritas Jasa Keuangan) - Sari Pebriana Riska; Rasuli M; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this study was to determine the influence of experience,observing on legal standards, reputation, independence and a strong commitmentto client satisfaction. The population in this study are company leaders andfinancial managers who work for non-bank financial industry companies inPekanbaru which are listed in the Financial Services Authority (OJK). This studyuses a survey method. The total respondents used in this study were 46respondents (57.5%). The analysis method is the Multiple Regression methodusing SPSS (Stastical Product and Service Solutions) version 22. The results ofthis study show experience, adhere to the HK standards, independence and strongcommitment affect client satisfaction. The coefficient of determination in thisstudy was 86.4%. The four independent variables together influence thedependent variable by 86.4%, while 13.6% is influenced by other obscurevariables.Keywords : Influence Of Experience, Observing On Legal Standards,Reputation, Independence, Strong Commitments And ClientSatisfaction.